2008
DOI: 10.1524/zkri.2008.0032
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of crystalline nitrosyl compounds

Abstract: Nitrosyl linkage isomer compounds are investigated with density functional theory for realistic crystal structures. As compared to free anion models, significant differences are found for various properties. At the metastable state S1, a crystal environment contribution of 30-40 cm À1 to the red shift exists. The barrier against thermal decomposition of S1 in SNP is significantly lowered by 300 meV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Overall, the present method has been demonstrated to be in excellent agreement for the ground-state energetics of molecules in a large database (Delley, 2006). The corresponding energy surface gives an excellent account of structural and vibrational properties of other nitrosyl compounds (Delley, 2008).…”
Section: Dft Calculations For the Solid Statementioning
confidence: 68%
See 1 more Smart Citation
“…Overall, the present method has been demonstrated to be in excellent agreement for the ground-state energetics of molecules in a large database (Delley, 2006). The corresponding energy surface gives an excellent account of structural and vibrational properties of other nitrosyl compounds (Delley, 2008).…”
Section: Dft Calculations For the Solid Statementioning
confidence: 68%
“…Helpful in this context are simulations of the local structural changes as a function of population number in order to find whether the novel structure can be detected with the planned measurement (Schefer et al, 2008). An important tool to further identify and determine lightinduced structural changes is density functional theory (DFT) calculations (Delley et al, 1997;Coppens et al, 2002;Delley, 2008;Ishikawa & Tanaka, 2008;Sizova et al, 2008). The validity of such calculations depends on the functional used and whether they are performed only for the molecular ion with an assumed charge background for charge compensation or whether they are made for all atoms in the complete solid state.…”
Section: Introductionmentioning
confidence: 99%
“…In these systems the barrier to rotation about the Ru-͑SO͒ bond ͑that is, to change of the N-Ru-S-O torsion angle͒ is known to be low so that crystal packing effects are important in determining the preferred orientation of the bound S-O linkage in the 2 excited state. 12,17 As a result, we expect to find two local energy minima, 180°apart, for the bound S and O atoms. Associated with each of these are a further two minima for the free O atom, as expected by the pseudosymmetry of the geometry.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…16 Comparison of gas phase with solid-state calculations has previously shown that in NO complexes the crystal surroundings have a small but important influence over the energy landscape of isomerization, in particular, influencing the barriers associated with rotation about the metal-ligand axis in the side-bound state. 17 In this paper we focus on the triatomic ligand SO 2 , in which the additional, free oxygen atom greatly increases the likelihood of steric interactions between the side-bound state and its crystal surroundings. The "reaction cavity" in which the ligand rotates is capable either of increasing or decreasing observed photoexcitation levels, as work on NO 2 complexes has demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…MLCT or d!d transition) and the presence of a minimum in the excited-state potential between the GS and MS2 or MS1, both of these being of purely unimolecular origin. It has further been shown by theoretical density functional theory studies (Delley, 2008) that, although the global behaviour is retained, the crystal environment significantly influences the properties of nitrosyl compounds, especially the vibrational properties of the NO ligand (i.e. the shift of the NO stretching frequency on going from the GS to MS1 or MS2), as well as the configuration energy and transition state energy along the photolinkage isomerism path on the energy hypersurface.…”
Section: Figurementioning
confidence: 99%